“What does sexuality in early childhood even look like? What is it?”: A qualitative exploration of early childhood professionals’ navigation of sexual development - Johnson-Olthoff, Misti L. (My University, 2026)
Early childhood professionals (ECPs), alongside parents and caregivers (PCGs), play a critical role in the co-socialization of sexuality throughout early childhood. However, there is limited literature that critically examines ECPs’ preparedness and experiences in navigating early childhood sexuality based on the comprehensive sexuality education (CSE) topics and methods within their pre-service teacher education preparation programs (TEPP) for early care and education. As such, I addressed this gap by qualitatively exploring 1) ECPs’ educational exposure, 2) professional experiences, and 3) recommendations for improving early childhood sexual education in TEPP based on their lived experiences. Guided by an inductive, exploratory, atheoretical approach, I conducted interviews with seven ECPs (aged 33-54) who all identified as White/Caucasian, Cisgender women with a range of 24 years of professional experience. Using an inductive framework and an Interpretive Phenomenological Analysis (IPA) approach (Smith & Fieldsend, 2021) the coding team identified five major themes that contributed to a deeper understanding of ECPs’ educational journeys, lived experiences, and recommendations: 1) (Non)Separation of Personal and Professional Self, 2) Socialized Silence, 3) ECP Continuum, 4) Preparedness for Real-Time Navigation of CSE, and 5) Recommendations. Overarchingly, these findings demonstrate a lack of educational opportunities and ECP preparedness that support the need for a reconceptualization of sexuality within early childhood education. These findings highlight the challenges that ECPs face while navigating normative and non-normative early childhood sexuality topics with not only children in their care, but also parent-caregivers and larger socio-political climates. Implications from this research are important for supporting ECPs within their TEPP but also across their careers as they remain co-socializers of sexuality and support whole-child development.
Keywords: Early childhood; Sexuality development; Sexual literacy; Sexual communication; Teacher education preparation program; Socialization